THE ROLE OF THE INDEPENDENT CURRICULUM IN IMPROVING THE QUALITY OF STUDENTS TO MOVE TOWARDS A GOLDEN INDONESIA 2045 - Nur Laili, Alivia Novita; Muhartono, Djoko Siswanto; Prangdicha, Bryant; Anggaini, Veronika Kiky (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2025)
This study aims to analyze the role of the Independent Curriculum in improving the quality of students and identify the positive impact of the implementation of the Independent Curriculum on the learning achievement and quality of students at SDN Banyu Urip 3, Surabaya City, towards the vision of a Golden Indonesia 2045. The data sources used in this study consist of secondary data, including documents related to the Independent Curriculum, student learning outcome reports, and information about the profile of SDN Banyu Urip 3. To collect data, this study uses documentation, interview, and observation techniques, with a focus on the implementation of the Independent Curriculum among students of SDN Banyu Urip 3. The data that has been collected will be analyzed systematically and objectively using qualitative descriptive analysis techniques. The results of this study will be presented based on data analysis that shows that the implementation of the Independent Curriculum has a positive impact on learning achievement and character development of students. The conclusion of this research will be formulated based on the analysis of the data and findings that have been obtained, which confirms that the Independent Curriculum at SDN Banyu Urip 3 is able to form the profile of Pancasila students who are ready to face the challenges of global competition. Thus, we can contribute to realizing the vision of Golden Indonesia 2045 through the development of quality, competent, and highly competitive human resources.